The Presence of Midrashim in Christmas Chronicles by Clarice Lispector - Botler, Laís Maria Rosal (2021)
Judaism never appears explicitly in Clarice Lispector's literature. However, as shown by Gilda Szklo (1989), Nelson Vieira (1989) and Berta Waldman (2011; 2014), the Jewish influence can be perceived in different ways in Clarice's writing. In this work, we will analyze the presence of midrashim in the representation of Christmas in the chronicles “Anunciação”, “A virgem em todas as mulheres”, “Ele seria alegre” e “A humildade de São José”.